2013
DOI: 10.1016/s1474-4422(12)70310-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and prognostic factors for long-term outcome in patients with anti-NMDA receptor encephalitis: an observational cohort study

Abstract: Background Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune disorder in which the use of immunotherapy and the long-term outcome have not been defined. Methods In this multi-institutional observational study (2007-2012), all patients with GluN1 antibodies were assessed at symptom onset and 4, 8, 12, 18, and 24 months using the modified Rankin Scale (mRS). Treatment included first-line immunotherapy (steroids, intravenous immunoglobulin, plasmapheresis), second-line immunotherapy (ritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

179
3,548
51
189

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 2,564 publications
(4,130 citation statements)
references
References 22 publications
179
3,548
51
189
Order By: Relevance
“…Therapeutic intervention targeting B cells and plasmablasts by two different agents, rituximab and tocilizumab,4 theoretically allows the evaluation of bortezomib efficacy by targeting long‐lived plasma cells. Follow‐up was continued for long enough (13–20 months post‐onset) to evaluate the mRS score improvement considering the disease course of anti‐NMDAR encephalitis 1. However, several limitations of this study should be considered when interpreting the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic intervention targeting B cells and plasmablasts by two different agents, rituximab and tocilizumab,4 theoretically allows the evaluation of bortezomib efficacy by targeting long‐lived plasma cells. Follow‐up was continued for long enough (13–20 months post‐onset) to evaluate the mRS score improvement considering the disease course of anti‐NMDAR encephalitis 1. However, several limitations of this study should be considered when interpreting the results.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients with autoimmune encephalitis respond to immunotherapy,1, 2, 3 a small, but significant, number of patients show an insufficient response even after aggressive immunotherapy; therefore, several treatment options are being explored 4, 5, 6. Long‐lived plasma cells that can survive without cell division and continuously secrete autoantibodies are considered to contribute to the poor clinical course in the patients, given their known resistance to B‐cell depleting agents, conventional immunosuppressants, and antiproliferative agents 7…”
Section: Introductionmentioning
confidence: 99%
“…Within the first 4 weeks of symptom onset, more than 40% of the patients with anti‐NMDAR encephalitis experience autonomic symptoms including hyperthermia, tachycardia, hypersalivation, bradycardia, hypertension, and hypotension 1, 3, 5. Although hypersalivation is one of the main autonomic dysfunctions in anti‐NMDAR encephalitis, there has been no clear consensus regarding which treatment is better for controlling hypersalivation.…”
Section: Discussionmentioning
confidence: 99%
“…By the first‐line immunotherapy (steroids, immunoglobulins, or plasma exchange) and second‐line immunotherapy (rituximab or cyclophosphamide), about 80% of patients with anti‐NMDAR encephalitis recovers favorably to be able to look after own affairs without assistance 5. However, 7% of the patients still die due to complications such as autonomic dysfunction, pneumonia, hypoventilation, rhabdomyolysis, or status epilepticus 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Reported relapse rates range between 12% and 24%, more often in those without teratoma [4]. The largest cohort study to date of 577 patients reported 53% recovery based on the modified Rankin Scale, and 97% of those who improved had good outcome at 24 months [8]. …”
Section: Treatmentmentioning
confidence: 99%